The influence of internal political dynamics on China's foreign policy - Vorel, Štěpán; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The thesis examines the foreign policy decision-making process of the Chinese Communist Party (CCP) using a neoclassical realist (NR) approach. The period under examination is from 2012 to the present. The thesis has two main parts: chapter one, on theory and methodology, explores the benefits and drawbacks of neoclassical realism in general, as well as the NR decision-making process specifically. The paper uses a ‘soft positivist’ approach to map out the different intervening variables that influence China’s leadership, as well as a case study of the ‘Taiwan question’ to illustrate the whole process. Chapter two then puts the theory and methodology of chapter one into practice. It first describes the four NR intervening variables as they appear in China, i.e. the CCP (domestic institutions and strategic culture), Xi Jinping (leader images and strategic culture), China’s material security challenges (state-society relations), and China’s economy (also state-society relations). After thus setting the stage, chapter two then moves on to explain the realities of Cross-Strait relations using the findings of the preceding sub-section. The thesis concludes that China under Xi has, and will likely continue to, pursue a foreign policy strategy that is somewhere between optimal and slightly overactive vis-a-vis Taiwan.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses